Synthesis of Sugar-Derived Triazole- and Pyridine-Based Metal Complex Ligands - Kraft, Jochen; Schmollinger, Daniel; Maudrich, Jakob; Ziegler, Thomas (Synthesis, 2015)
A series of 30 bi- and tridentate ligands for metals were prepared by copper-catalyzed coupling (CLICK reaction) of 2-ethynylpridine, 2-ethynyl-5-nitropyridine, 2-ethynylquinoline, and 2,6-diethynylpyridine with 12 protected glycosyl azides in the gluco and galacto series and 2 benzyl azides. The 1,2,3-triazole-linked glycoconjugates prepared were used as ligands for the copper-catalyzed addition of phenylacetylene to N-benzylideneaniline to give chiral N-(1,3-diphenylprop-2-yn-1-yl)aniline.
Keywords: asymmetric catalysis; azides; carbohydrates; enantioselectivity; glycoconjugates